2015
DOI: 10.1039/c5ee01917f
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient polymer solar cells cast from non-halogenated xylene/anisaldehyde solution

Abstract: Several high performance polymer:fullerene bulk-heterojunction photo-active layers, deposited from the non-halogenated solvents o-xylene or anisole in combination with the eco-compatible additive p-anisaldehyde, are investigated. The respective solar cells yield excellent power conversion efficiencies up to 9.5%, outperforming reference devices deposited from the commonly used halogenated chlorobenzene/1,8-diiodooctane solvent/additive combination. The impact of the processing solvent on the bulk-heterojunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 139 publications
(118 citation statements)
references
References 37 publications
(79 reference statements)
4
113
1
Order By: Relevance
“…More encouragingly, in addition to a slightly higher PCE than that of devices processed with the widely used halogenated DCB/DIO system ( Figure 3 ), the device fabricating process was greatly simplifi ed. Very recently, Colsmann et al [ 49 ] also found that the non-halogenated solvent XY in combination with the eco-compatible additive …”
Section: General Processing Methods Of Opvs Featuring Well-known Pbdtmentioning
confidence: 95%
“…More encouragingly, in addition to a slightly higher PCE than that of devices processed with the widely used halogenated DCB/DIO system ( Figure 3 ), the device fabricating process was greatly simplifi ed. Very recently, Colsmann et al [ 49 ] also found that the non-halogenated solvent XY in combination with the eco-compatible additive …”
Section: General Processing Methods Of Opvs Featuring Well-known Pbdtmentioning
confidence: 95%
“…1d. Importantly, the co-solvent p-anisaldehyde exhibits a comparatively low boiling point, ensuring its complete evaporation after thin-film deposition, 31 whereas common other co-solvents such as 1,8-diiodooctane may partly remain within the bulkheterojunction where they may accelerate device deterioration. 30 To investigate the thermal stability of the solar cells, we annealed the samples at 120°C for 2 h, which is often considered the critical condition for industrial relevant lamination processes for consumer products.…”
Section: Resultsmentioning
confidence: 99%
“…[65,66] Processing methods and conditions, e.g., vapor deposition or solution processing, influence materials properties and thus have to be taken into account when modeling the morphologies of organic semiconductors. [67,68] Small variations in the chemical structure of molecules [39] as well as the solvents used in solution processed thin films [69] can also alter the morphology of the material. [18] Various properties of these materials depend on the detailed morphology, which in turn varies with processing conditions and kinetics.…”
Section: Morphologymentioning
confidence: 99%